KINETICS OF COLOUR CHANGE OF TOMATOES DURING DRYING - A. Unadi; R.J. Fuller; R.H. Macmillan (Indonesian Agency for Agricultural Research and Development, 2001)
Colour is one of the pharameters determining the quality of dried tomatoes. The changes in colour of the skin of tomatoes during drying in an experimental dryer at various temperatures were measured every two hours by using Minolta CR 200 colorimeter and the colours were represented in Hunter-Lab scale. The objective of this research was develop a model for predicting colour changes of tomatoes during drying. The decrease in darkness as represented by dL value varied from 10 to 16%, while decrease in chroma value (dL) varied from 20 to 37% of initial values. An empirical logarithmic equation with six constants was derived to fit the data of chroma changes during drying at various temperature and times. The model of colour change of tomatoes can be used for determining the optimum drying temperature to produce acceptable colour of dried tomatoes at reasonable cost.